12.8k views
3 votes
Solve. -6x^2 – 2 – 3x = -8​

User Thotep
by
5.9k points

1 Answer

3 votes

Answer:

Add 8 to both sides of the equation.

−6x²−2−3x+8=0 Add −2and 8.

−6x²−3x+6=0

Factor −3 out of −6x²−3x+6.

−3(2x²+x−2)=0

Divide each term by −3 and simplify.

2x²+x−2=0

Use the quadratic formula to find the solutions.

(−b±√b2−4(ac))/2a

Substitute the values a=2 , b=1, and c=−2 into the quadratic formula and solve for x .

(−1±√12−4⋅(2⋅−2))/(2⋅2) Simplify.

x=−1±√174

The final answer is the combination of both solutions.

x=(−1−√17)/4, (−1+√17/)4

The result can be shown in multiple forms.

Exact Form:

x=(−1−√17)/4, (−1+√17)/4

Explanation:

User Tom Finet
by
5.4k points